Diffuse Oligosymptomatic Caroli’s Disease: Case Report - Y, Lemfadli; S, Bouchrit; A, Ait Errami; S, Oubaha; Z, Samlani; K, Krati (Bangladesh Journal of Medicine, 2020)
This article describes a case of Caroli’s disease in a 53-year-old female patient who complained nonspecificabdominal pain without cholestasis or cholangitis. Ultrasound and hepatic magnetic resonanceimaging showed segmental saccular dilations connected to intrahepatic bile ducts without hepaticfibrosis. This clinical case shows the possibility of having oligosymptomatic forms in the diffuse formsof Caroli disease, therefore the interest to consider this diagnosis in case of non-specific abdominalsigns and to request a hepatic ultrasound. Bangladesh J Medicine July 2020; 31(2) : 107-110